Investigation of the accuracy of close-range photogrammetry – a 3D printing case study - Lužanin, Ognjan; Puškarević, Irma (Journal of Graphic Engineering and Design, 2023)
3D scanning of physical objects is one of the frequently used methods for generating input data for 3D printing process. Close-range photogrammetry represents a cost-efficient alternative to conventional 3D scanning. However, one of the basic problems in application of this method is accuracy, especially in the case of small objects with complex geometry. In this case study, a 3D-printed object of small dimensions was used to test the accuracy and precision of close-range photogrammetry. CAD Inspection was used to obtain measurements of the scanned model and compare it with the original CAD model, while the results were statistically analyzed. The results of statistical analysis showed that the scanning accuracy in this experiment did not depend on the particular cross-section of the model, while the precision of 3D scanning depended on the selection of cross-sectional profile curve.